The dynamic relationship between TFP and human capital inequality : evidence from ASEAN countries - Hong, Du Yu; Abu Hassan Shaari Md. Nor; Tamat Sarmidi (Penerbit Universiti Kebangsaan Malaysia, 2018)
The study investigates the long-run equilibrium relationship between human capital inequality and cumulative TFP growth rate using data for a panel of 5 selected ASEAN countries over the period of 1990 to 2014. Both the first-generation and second-generation panel unit root tests are involved and the long-run equilibrium relationships among variables are confirmed by using the Pedroni-type panel cointegration tests and the Westerlund-type panel cointegration estimator. Using the FMOLS and DOLS estimators, the results for the whole panel, human capital inequality is negatively affecting the cumulative TFP growth rate suggesting that the unequal distribution of human capital is harmful to regional TFP growth and an improvement in human capital inequality will promote TFP growth. However, homogenous effects of all individual countries are impractical and the results of the relationship between human capital inequality and TFP growth rate for individual countries present heterogeneity.